Association of perceived neighborhood air quality problems with attempt to quit cigarette smoking: a cross-sectional study in Texas - Chandra, Monalisa; Fokom Domgue, Joel; Yu, Robert; Shete, Sanjay (Frontiers in Public Health, 2024)
Background: Cigarette smoking is the major preventable cause of premature deaths in the United States. Attempting to quit smoking is an important step towards smoking cessation. Although it has been studied extensively, limited information on the association between attempts to quit smoking and neighborhood air quality problems is available. Therefore, we examined the association between attempts to quit smoking in the past year and perceived neighborhood air quality problems among adult Texans who smoke. Methods: In 2018, a cross-sectional multistage area probability design-based survey was administered to collect sociodemographic, behavioral, and health-related information from a representative sample of 2050 Texas residents. The current study included 486 adult respondents who reported smoking within the past 12 months. The association between attempts to quit smoking and perceived neighborhood air quality (measured by self-reported problems with neighborhood air quality) was examined using a population-weighted multivariable logistic regression analysis. Result: Overall, 60.7% of the 486 respondents attempted to quit cigarette smoking. The prevalence of attempting to quit was 74.6% for those reporting perceived neighborhood air quality problems. In the multivariable analysis, a higher likelihood of attempting to quit smoking was found among individuals with perceived neighborhood air quality problems (AOR: 1.906 [1.104-3.289]) and those who were married or living as married (AOR: 1.876 [1.161-3.033]). The likelihood of attempts to quit smoking was lower among males (AOR: 0.629 [0.397-0.995]) and decreased with age (AOR: 0.968 [0.951-0.984]). Discussion: The perceived neighborhood air quality problems were found to independently predict attempts to quit cigarette smoking in Texas. To encourage quitting smoking among individuals living in neighborhoods with poor air quality, such neighborhoods should receive tailored and evidence-based interventions to improve community education, social support, and healthcare professionals’ assistance to quit smoking.